2005
DOI: 10.1359/jbmr.050718
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-23 Is Regulated by 1α,25-Dihydroxyvitamin D

Abstract: Serum FGF-23 regulation was studied in patients with hypoparathyroidism or pseudohypoparathyroidism treated with calcitriol. Serum FGF-23 levels changed in parallel in response to changes in serum 1,25-D, suggesting that FGF-23 may be regulated by 1,25-D. In addition, the phosphaturic effect of FGF-23 may be diminished in the absence of PTH action on the kidney. Introduction: Fibroblast growth factor (FGF)-23 is a recently described hormone that has been shown to be involved in the regulation of phosphate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 37 publications
6
69
1
1
Order By: Relevance
“…Although F e PO 4 increased within the VIT-D group, there were no between-group differences in F e PO 4 , serum phosphate, PTH, or calcium levels. Prior studies have shown that 1,25(OH) 2 D increases FGF23 synthesis and its circulating levels (13,14,25). This study is the first to show that ergocalciferol administration is associated with increased FGF23 production; however, in this model, we were unable to determine if the increase was because of ergocalciferol, 25OHD, or 1,25(OH) 2 D.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although F e PO 4 increased within the VIT-D group, there were no between-group differences in F e PO 4 , serum phosphate, PTH, or calcium levels. Prior studies have shown that 1,25(OH) 2 D increases FGF23 synthesis and its circulating levels (13,14,25). This study is the first to show that ergocalciferol administration is associated with increased FGF23 production; however, in this model, we were unable to determine if the increase was because of ergocalciferol, 25OHD, or 1,25(OH) 2 D.…”
Section: Discussioncontrasting
confidence: 56%
“…1,25-Dihydroxyvitamin D [1,25(OH) 2 D], dietary phosphate, and circulating phosphate are key regulators of FGF23 (12)(13)(14)(15)(16)(17)(18). However, it is unknown if vitamin D (either ergocalciferol or cholecalciferol) affects FGF23 secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning humans, there are data that correlate calcitriol with FGF23 in patients with renal impairment (17) and in patients with hypoparathyroidism (18), while data relating calcitriol with FGF23 in healthy individuals do not exist as far as we are aware.…”
mentioning
confidence: 95%
“…[17][18][19] In addition, FGF-23 is positively regulated by 1,25(OH) 2 D, PTH, and Klotho. [20][21][22] This complexity of the PO4-FGF-23 cybernetic system, coupled with the indeterminate evidence for an FGF-23 response to phosphate loads in humans, makes it difficult to predict the relative importance of these four hormones and the temporal relation of their response in the elimination of a PO4 load.…”
mentioning
confidence: 99%